The role of GABA in type 1 diabetes - Mick, Gail J.; McCormick, Kenneth L. (Frontiers in Endocrinology, 2024)
Gamma aminobutyric acid (GABA) is synthesized from glutamate by glutamic decarboxylase (GAD). The entero-pancreatic biology of GABA, which is produced by pancreatic islets, GAD-expressing microbiota, enteric immune cells, or ingested through diet, supports an essential physiologic role of GABA in the health and disease. Outside the central nervous system (CNS), GABA is uniquely concentrated in pancreatic β-cells. They express GAD65, which is a type 1 diabetes (T1D) autoantigen.Glutamate constitutes 10% of the amino acids in dietary protein and is preeminently concentrated in human milk. GABA is enriched in many foods, such as tomato and fermented cheese, and is an over-thecounter supplement. Selected microbiota in the midgut have the enzymatic capacity to produce GABA.Intestinal microbiota interact with gut-associated lymphoid tissue to maintain host defenses and immune tolerance and are implicated in autoimmune disease. Although GABA is a widely known inhibitory neurotransmitter, oral GABA does not cross the blood brain barrier. Three diabetes-related therapeutic actions are ascribed to GABA, namely, increasing pancreatic β-cell content, attenuating excess glucagon and tamping down T-cell immune destruction. These salutary actions have been observed in numerous rodent diabetes models that usually employed high or near-continuous GABA doses. Clinical studies, to date, have identified positive effects of oral GABA on peripheral blood mononuclear cell cytokine release and plasma glucagon. Going forward, it is reassuring that oral GABA therapy has been well-tolerated and devoid of serious adverse effects.